Some policies and laws on freelance workers at land border areas in Vietnam and recommendations for improvement in the coming time - Pham Thi Huong Lan, Lan (Technium Social Sciences Journal, 2024)
Vietnamese freelance workers who work in land border areas of neighboring countries are quite large in number, thus the policies and laws on labor at the land border as well as issues of ensuring the rights of workers and labor management require more attention. In this article, the author will discuss some of the current status of policies and laws in Vietnam on freelance workers at the land border and solutions to improve policies, laws and management capacity in the coming time for Vietnamese people working in neighboring countries.